'I'm going to learn how to run quick': exploring violence directed towards staff in the Emergency Department. Issue 11 (25th October 2012) - Knowles, Emma; Mason, Suzanne M; Moriarty, Faye
Abstract : Background: The National Health Service (NHS) depends on a highly skilled workforce. Anything threatening the well-being of that workforce threatens the delivery of healthcare. Violence and aggression directed towards healthcare professionals is a longstanding problem within the NHS, and is particularly acute in the Emergency Department (ED). This study examined ED staff perceptions and experiences of violent behaviour directed towards them within the ED. Methods: Four EDs were selected to take part in the study. A period of up to 3 days was spent in each ED in order to collect data. Mixed methods were utilised to capture data: incident report forms were examined to establish the reported incidence of violence/aggression, ethnographic observations were noted, and staff interviews were undertaken. Results: Staff defined violence as having both verbal and physical dimensions, and felt that verbal aggression was a regular occurrence. Staff communicated a number of reasons, which went beyond excessive alcohol consumption, as to why EDs are particularly susceptible to aggression/violence. There was variation in reporting behaviour between departments and individuals. This appeared to be linked to the presence of security staff within the hospital, staff disillusionment with the reporting process, and issues with the incident report form itself. Conclusions: This study adds to current evidence regarding how staff perceive and experience violence in the ED. Given the variation in reporting behaviour, national figures on violence within the NHS are likely to be underestimated. More research is needed to understand the true prevalence of violence occurring in the ED.